In Vitro Maturation of a Humanized Shark VNAR Domain to Improve Its Biophysical Properties to Facilitate Clinical Development - Steven, John; Müller, Mischa R.; Carvalho, Miguel F.; Ubah, Obinna C.; Kovaleva, Marina; Donohoe, Gerard; Baddeley, Thomas; Cornock, Dawn; Saunders, Kenneth; Porter, Andrew J.; Barelle, Caroline Jane (Frontiers in Immunology, 2017)
Molecular engineering to increase the percentage identity to common human immunoglobulin sequences of non-human therapeutic antibodies and scaffolds has become standard practice. This strategy is often used to reduce undesirable immunogenic responses, accelerating the clinical development of candidate domains. The first humanized shark variable domain (VNAR) was reported by Kovalenko and colleagues and used the anti-human serum albumin domain (HSA), clone E06, as a model to construct a number of humanized versions including huE06v1.10. This study extends this work by using huE06v1.10 as a template to isolate domains with improved biophysical properties and reduced antigenicity. Random mutagenesis was conducted on huE06v1.10 followed by refinement of clones through an off-rate ranking-based selection on target antigen. Many of these next-generation binders retained high affinity for target, together with good species cross reactivity. Lead domains were assessed for any tendency to dimerize, tolerance to N and C-terminal fusions, affinity, stability and relative antigenicity in human dendritic cell assays. Functionality of candidate clones was verified in vivo through the extension of serum half-life in a typical drug format. From these analyses the domain, BA11, exhibited negligible antigenicity, high stability and high affinity for mouse, rat, and human serum albumin. When these attributes were combined with demonstrable functionality in a rat model of PK, the BA11 clone was established as our clinical candidate.